A survey of environmental DNA in South Australia Police facilities. (December 2015) - Henry, Julianne; McGowan, Pip; Brown, Cheryl
Abstract: Crime scene exhibits are sometimes examined and sampled in South Australia Police (SAPOL) facilities prior to submission to Forensic Science SA (FSSA) for DNA profiling. There are 18 such facilities; 10 metropolitan and 8 regional. FSSA has employed an environmental DNA monitoring program since 2008, as part of its quality assurance system. This program aims to measure the background levels of DNA in areas where forensic evidence is collected, examined or processed, to ensure that the risk of DNA contamination is minimised through effective work practices and cleaning regimes. This is the first survey of environmental DNA across all SAPOL facilities and the results show that significant background DNA exists on a number of surfaces and items of equipment. This data is being considered by SAPOL and may facilitate improvements to examination areas and standard operating procedures.